Connectivity for Caribbean Countries : An Initial Assessment - Briceno-Garmendia, Cecilia (World Bank, Washington, DC, 2014)
Their vital relation with the Caribbean Sea is a defining factor for the many cultures, languages and countries that co-exist in the Caribbean. This factor acts as both the most important vehicle and as their most challenging obstacle to connect with the world, and represents the starting point for every single discussion around Caribbean states: the fact that they are sea-locked countries (for most), small economies, with a high level of vul¬nerability to natural disasters and a geographic location that calls for regional cooperation and integration. Two of these the fact that they are sea-locked and their location in the Caribbean pose critical and unchangeable barriers to maximizing the development of their infrastructure and connectivity. In consequence, exchanges of goods and services with the rest of the world are limited to air and maritime transport modes, logistics costs are gen¬erally higher, and they face a disproportionate risk disruption due to natural disasters. This all translates into a cost premium for developing both infrastructure and transport services, regardless of the degree of efficiency of the investment decision process. In the Caribbean Growth Forum (GCF), economic growth and competitiveness of member countries are in¬variably intertwined with air and maritime transportation.